Quick & clever drawing - Sanders, Michael , 1950- (Cincinnati, Ohio : David & Charles Book, 2009)
Offers an introduction to drawing. This work shares the author's many inventive and foolproof drawing techniques with many art materials - developed from years of teaching both beginners and improvers. Each chapter explores how to draw a popular subject, starting with art technique - focused exercises before moving on to a step-by-step drawing.
1. Starting to draw -- 2. Materials -- 3. Techniques -- 4. Working with colour -- 5. Start drawing -- 6. Project 1: land and sea -- 7. Project 2: buildings made easy -- 8. Project 3: trees in a landscape -- 9. Project 4: Venice scene -- 10. Project 5: Spanish scene -- 11. Project 6: portrait -- 12. A final word
Includes index
Keywords: Drawing -- Technique